Pulse Oximeter Design for SpO2 and BPM Recording on External Memory to Support the Covid-19 Diagnosis - Syaifudin Syaifudin; Triwiyanto Triwiyanto; Dinar Awalin Harditamara; Faraz Masood (Jurnal Teknokes, 2022)
COVID-19 (coronavirus disease) is an acute respiratory illness induced by exposure to coronavirus 2 in 2019 (SARS-CoV-2). WHO confirms that there were 1.8 million registered deaths in 2020 and that there were 3.5 million recorded deaths in 2021. People who are infected with SARS-CoV-2 without symptoms should have a pulse oximeter. Early detection of low oxygen levels in the blood can lead to fewer complications. Continuously decreasing oxygen saturation, if not controlled, will cause hypoxia (an abnormal respiratory circulation system condition that causes breathlessness). In normal conditions, oxygen levels and heart rate are related. When a person has a shortage of oxygen (breathlessness), their heart rate increases to supply the oxygen. Regulating heart rate can aid in the prevention of disorders such as arrhythmia, coronary heart disease, and hypertension. A pulse oximeter is used to measure the oxygen saturation in the blood and the patient's heart rate (BPM) with non-invasive methods. Conventional pulse oximeters do not support users by not having features such as medical records, which are required for further examination by a doctor. The purpose of this research is to make a pulse oximeter with external storage capability. The difference in wavelength between the red and infrared LED lights that will be captured by the photodiode is measured. SpO2 and HR values will be generated as a result of comparative measurements. Using a MAX30102 sensor to detect SpO2 and heart rate, and an Arduino Mega256 to process data for display on the TFT Nextion with Memory Card storage. By comparing the module to a conventional pulse oximeter, data was collected 10 times for each respondent. The maximum SpO2 error value is 0.43%, whereas the BPM parameter has the largest error value of 2.02% and the smallest error value of 0.01% based on the data collected. A significant error value is caused by finger movement. The module is usable, based on the results, because the maximum error tolerance for a pulse oximeter is 1% SpO2 and 5% BPM, according to the 2001 Ministry of Health Ministry's Guidelines for Testing and Calibrating Medical Devices.